A study of Malaysians’ intentions in using RFID tag as an electronic payment - Er, Boon Xin; Gan, Jie Min; Hing, Yoke Shan; Shen, Yu (2023)
In recent years, the Malaysian government has introduced RFID technology to replace the existing toll payment system. However, the adoption rate of RFID among Malaysian drivers is still low. This research investigates the factors that influence Malaysian drivers' intentions to use RFID as a payment method on highways using the Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). The research identifies six independent variables that may influence drivers' intentions toward RFID, including perceived ease of use, perceived usefulness, social influence, attitude, social media, and government support. A total of 400 questionnaires were collected, and the data underwent various statistical analyses including outer loadings analysis, reliability testing, discriminant validity testing, and bootstrapping. The results show that only perceived ease of use, perceived usefulness, and attitude have a positive and significant relationship with the intention to use RFID. Conversely, social media, social influence, and government support do not significantly influence intentions. The research suggests that merchants consider implementing RFID technology to enhance their services, and TNG Company should improve the user-friendliness, efficiency, and convenience of the technology. Additionally, the government can indirectly influence drivers' intention to use RFID by encouraging collaboration between SMEs and TNG Company, offering free installation services, and establishing a legal framework to enforce fraud and bad toll payment situations. The research acknowledges some limitations, including the sample size bias, the differences in RFID system availability across regions, and the framework's inability to measure actual usage behaviour. To improve future research, it is needed for a more representative sample across different age ranges, focusing on specific subgroups within the population, incorporating measures of actual usage behaviour, considering contextual factors, and conducting a comprehensive literature review. By addressing these limitations, researchers can produce more valuable insights that are applicable to the nation and population being studied.